DEVELOPMENT OF LEARNING ACTIVITIES BY USING MODEL BASED LEARNING ON THE TOPIC OF IMMUNE SYSTEM TO ENHANCE SYSTEMS THINKING ABILITY FOR ELEVENTH GRADE STUDENTS - Parmboon, Wanchanok; Sittisomboon, Monasit; Onthanee, Angkana (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were to 1) create and evaluate the effectiveness of learning activities by using Model Based Learning on the topic of immune system according to the criteria 75/75. 2) compared the system thinking ability between before and after using the learning activities by using Model Based Learning on the topic of immune system. 3) study the satisfaction of students with the learning activities by using Model Based Learning on the topic of immune system. The researcher followed the research processes of Research and Development. The sample group of 40 in eleventh grade students in the semester 2 of academic year 2022 at Bangkrathum Pittayakom School under The Secondary Educational Service Area Office Phitsanulok Uttaradit. The sample group was selected by using Sample random sampling. The scopes of the research tools were 1) the learning activities by using Model Based Learning on the topic of immune system. 2) the systems thinking ability test. 3) the satisfaction questionnaire of students to towards learning with learning activities by using Model Based Learning on the topic of immune system. The statistics used for data analysis were percentage, mean, standard deviation, efficiency (E1/E2) and hypothesis testing by using the t-test. The results were found that: 1) the learning activities by using Model Based Learning on the topic of immune system was at a highest level of appropriateness ( = 4.50, S.D.= 0.51) and efficiency at 75.23/75.31 which mean it met the criterion 75/75. 2) the systems thinking ability of students after using the learning activities by using Model Based Learning on the topic of immune system were higher than before learning at .05 statistic significant level. 3) the satisfaction of students towards learning activities by using Model Based Learning on the topic of immune system was at high level. ( = 4.33, S.D.= 0.69)